Long‐term outcome of endotherapy for pancreatic stones by using a dedicated pancreatic basket catheter. Issue 9 (22nd March 2021) - Saito, Tomotaka; Nakai, Yousuke; Mizuno, Suguru; Isayama, Hiroyuki; Sasahira, Naoki; Kanai, Sachiko; Noguchi, Kensaku; Sato, Tatsuya; Ishigaki, Kazunaga; Hakuta, Ryunosuke; Saito, Kei; Hamada, Tsuyoshi; et al.
Abstract: Background and Aim: Although endotherapy for pancreatic stones is less invasive compared with surgical interventions, its recurrence rate is high and residual pancreatic stones can be a cause of recurrence. We previously reported usefulness of a novel basket catheter with nitinol fine reticular structure for pancreatic stone retraction. In this retrospective study, we aimed to evaluate the long‐term outcomes of endotherapy for pancreatic stones with and without the use of this dedicated basket catheter. Methods: We retrospectively compared patients with symptomatic pancreatic stones who underwent the initial endotherapy between 2008 and 2019. The primary outcome was the symptomatic recurrence after complete stone clearance. Secondary outcomes were the rate of complete stone clearance, complications, risk factors for recurrences, and the treatment cost. Results: A total of 101 patients who underwent endotherapy for pancreatic stones were analyzed: 41 patients by using the dedicated basket catheter and 60 patients by only the conventional devices. The complete stone clearance was achieved in 87.8% in the dedicated basket group and 88.3% in the conventional device group. Symptomatic recurrence was observed in 16.7% of the dedicated basket group and 47.2% of the conventional device group ( P < 0.01). In the multivariate analysis, the use of the dedicated basket catheter was significantly associated with the reduced risk of symptomatic recurrence (hazard ratio, 0.40; 95% confidence interval, 0.15–0.92, P = 0.031). The complication rate and the cost were comparable between the two groups. Conclusion: The use of this dedicated pancreatic basket catheter significantly reduced symptomatic recurrence after complete pancreatic stone removal.